The Contemporary British Novel Since 1980
V, 250 p.
Keywords: Written by some of the world's finest contemporary literature specialists, the specially commissioned essays in this volume examine the work of more than twenty major British novelists, including Peter Ackroyd, Martin Amis, Iain (M.) Banks, Pat Barker, Julian Barnes, A.S. Byatt, Angela Carter, Janice Galloway, Kazuo Ishiguro, Hanif Kureishi, Ian McEwan, Salman Rushdie, Zadie Smith, Graham Swift, Rose Tremain, Marina Warner, Irvine Welsh and Jeanette Winterson. Focusing mainly on authors whose first novels have appeared since 1980, the essays provide expert and original analysis of the most recent trends in the theory and practice of contemporary British fiction, and are organized by these 4 major approaches: realism, postcolonialism, feminism and postmodernism.